HUBUNGAN ANTARA POLA ASUH DENGAN MOTIVASI BERPRESTASI PADA ANAK - Laurentia Sugianto; Setiasih Setiasih; Mary Philia Elisabeth (Perpustakaan Universitas Surabaya, 2020)
Parenting style has a very important role in supporting child’s achivement motivation because at this age they have orientation on achievement and capable of critical thinking. This study aims to determine the relationship between parenting style and achievement motivation in childhood. The subjects of this study were 84 subjects of tutoring center with an age range of 9 to 11 years and carried out incidental sampling. Parenting style scale made by Gafoor and Kurukkan (2014). Achievement motivation scale made by Steinmayr & Bergold (2016) and). Data were analyzed with nonparametric Spearman correlation. The resultsin this study indicate a significant positive relationship between the parenting style with achievement motivation (r = 0.591; 0.001 <0.050). Most of the subjects have a high level of responsiveness and demandingness with hope for success that is classified as high and fear of failure that is classified as low.